Teknik Pembinaan Kedisiplinan Santriwati Di Pondok Pesantren Putri Imam Syuhodo Tahun Pelajaran 2015/2016 - Muji Rahayu, Rina; , Drs. Saifuddin Zuhri, M.Ag (2016)
Discipline is one of the efforts to improve the character of children of the nation, with discipline all activities will run orderly and purposefuly. Imam Syuhodo Islamic boarding school is one of the Islamic educational institutions that builds Muslim's generation to become men of piety and have noble character. So that discipline is one of the keys to achieve it. The female teachers as the counselor at Imam Syuhodo Islamic Boarding School for Girls, have responsibilities in fostering discipline of the female students so that every activity in the boarding school runs well. Thus, this study examines "Coaching Techniques of Student Discipline for Girls at Imam Syuhodo Boarding School in 2015/2016". In this study, the problems studied are about the coaching techniques of student discipline for girls at Imam Syuhodo boarding school in 2015/2016 and factors that driving and inhibiting in maintaining discipline of some students for girls at Imam Syuhodo boarding school in 2015/2016. Thus, this study aims to describe the coaching techniques of discipline, and the factors that driving and inhibiting in fostering students of discipline for girls at Imam Syuhodo Islamic boarding school in year 2015/2016. This study is a field research with a qualitative approach. The methods used in collecting data are interview, documentation and observation. Whereas, the methods of data analysis used in this study are the qualitative and inductive descriptive analysis techniques. Based on the data analysis, the results of this study suggest that the coaching techniques of student discipline for girls at Imam Syuhodo boarding school in 2015/2016 are: 1). Enforcing regulations, 2). Giving warnings and penalties, 3). Giving rewards, 4). Fostering through a moral approach or the provision of advice, 5). Giving a good example, 6). In cooperation with the organization of Muhammadiyah Student Association in Imam Syuhodo Islamic Boarding School. Meanwhile, the driving and inhibiting factors are: 1). Internal factors, comprised of personal factors derived from both sides, the teachers and the students themselves, 2). External factors, consist of family factors and environmental factors of the students.